1985
DOI: 10.1176/ajp.142.8.917
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and outcome in brief focal dynamic therapy

Abstract: In an attempt to test the hypothesis that therapist empathy is an important variable in successful dynamic therapy, the authors collected outcome measures and empathy ratings in the brief focal dynamic therapy of 59 patients. There was no significant agreement among patients, therapists, and clinical supervisors when they used the same scale to rate therapist empathy for the same sessions. Only the patients' ratings correlated significantly with some of the outcome measures, and they added modest but statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is not unusual for therapists and clients to have different views of the therapy relationship. For example, when therapists, clients, and supervisors were rated therapist empathy during the same session, there was no significant agreement among clients, therapists, or supervisors on ratings of therapist empathy (Free, Green, Grace, Chernus, & Whitman, 1985; Squier, 1990).…”
Section: Discussionmentioning
confidence: 96%
“…It is not unusual for therapists and clients to have different views of the therapy relationship. For example, when therapists, clients, and supervisors were rated therapist empathy during the same session, there was no significant agreement among clients, therapists, or supervisors on ratings of therapist empathy (Free, Green, Grace, Chernus, & Whitman, 1985; Squier, 1990).…”
Section: Discussionmentioning
confidence: 96%
“…One interpretation of the findings was that the poor associations between residents’ self-reported empathy and simulated patients’ assessments could be a contextual artifact due to the use of simulated versus real patients and short encounter times (30). It has been suggested that the link between patients’ perceptions and clinicians’ self-reported empathy could be strengthened by better training in how to communicate empathic understanding to patients (31). Empathic engagement requires a reasonable time to develop which cannot be fully formed in a short period of a single clinical encounter with simulated patients in OSCE situations (28,32).…”
Section: Correlation With Clinician’s Self-reported Empathymentioning
confidence: 99%
“…The controversial findings might be due to the biased patient perception of provider empathy in comparison to provider self-assessed since empathy determination requires certain time to develop and might be skewed due to limited time within a single patient encounter [ 7 ]. This could particularly be occurring in stressful environments where there is a lack of relationship built between patients and providers on empathic understanding [ 9 , 12 ]. The JSE was initially derived and used for empathy evaluations of health professions students and proved to be valid in terms of its construction, internal consistency, prediction, and test-retest reliabilities [ 8 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%